(untitled) (Research, Society and Development, 2021)
Objective: To describe the incidence and mortality of congenital syphilis in the period from 2009 to 2018. Methodology: Epidemiological, descriptive study, with a cross-sectional design. Population composed of 1876 notified cases of congenital syphilis in Maceió residents. The data were extracted from the Health Information Systems. For statistical analysis, the chi-square test, ANOVA and Linear regression were used. The survey was approved under opinion nº 3.138.921. Results: The incidence of congenital syphilis has shown an increasing trend in the last 10 years. 32 deaths were recorded, which corresponded to a lethality of 1.7 deaths / 100 cases of congenital syphilis. Infant mortality showed the highest rate in 2012, 0.47 deaths / 1000 live births, maintaining a regular pattern between the years evaluated. Conclusion: The high incidence of congenital syphilis in Maceió represents a challenge for public health and requires strategies to improve prenatal care, in order to decrease mortality rates due to this cause.